Spectrum of Cranial Ultrasound in Neonatal Seizurea Cross-sectional Study in a Tertiary Care Paediatric Hospital in Bangladesh (Northern International Medical College Journal, 2025)
Background: Diseases of central nervous system of neonate commonly manifested by seizure, recurrence of which causes permanent damage of central nervous system, increase the risk of epilepsy and cognitive disabilities. Cranial Ultrasonography shows pathologic brain finding and prompt treatment will prevent further damage of immature brain. This study aims to assess cranial ultrasonography findings in neonatal seizure. Methods: This hospital based prospective observational cross-sectional study has been conducted in the Department of Paediatrics, Dhaka Shishu Hospital from January to July 2020. Total 60 neonates presenting with seizure were enrolled in the study by random sampling. Baseline characteristics of convulsing neonates including sex, gestational age, weight, head circumference was recorded at admission. Clinical details of each seizure episode were reported by caregiver and attending doctor i.e., age at onset of seizure, duration of seizure, number and type of seizure. Ultrasonography of Brain was done every neonate having seizure. Informed written consent from caregiver was taken before enrolment. Results: Among 60 neonates, Cranial ultrasound showed pathologic finding in 38(63.3%) cases. Hypoxic ischemic change was the commonest finding (68.4%), followed by raised parenchymal echotexture (23.7%), intracranial haemorrhage (2.6%), hydrocephalus (2.6%) and partial agenesis of corpus callosum (2.6%). Conclusion: Hypoxic ischemic change was the commonest pathologic finding of cranial ultrasonography.Northern International Medical College Journal Vol. 14 No. 1-2 July 2022-January 2023, Page 616-618